1987
DOI: 10.1128/aem.53.1.198-200.1987
|View full text |Cite
|
Sign up to set email alerts
|

Arginine deiminase system and bacterial adaptation to acid environments

Abstract: The arginine deiminase system in a variety of streptococci and in Pseudomonas aeruginosa was found to be unusually acid tolerant in that arginolysis occurred at pH values well below the minima for growth and glycolysis. The acid tolerance of the system allowed bacteria to survive potentially lethal acidification through production of ammonia to raise the environmental pH value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(96 citation statements)
references
References 11 publications
2
94
0
Order By: Relevance
“…The enhanced viability might be attributed to the pH rise due to ammonia production by the ADI pathway as mentioned for S. sanguis [8]. These authors showed that the enzymes of the ADI pathway have their optimal pH of activity at lower values than other intracellular enzymes.…”
Section: Discussionmentioning
confidence: 85%
“…The enhanced viability might be attributed to the pH rise due to ammonia production by the ADI pathway as mentioned for S. sanguis [8]. These authors showed that the enzymes of the ADI pathway have their optimal pH of activity at lower values than other intracellular enzymes.…”
Section: Discussionmentioning
confidence: 85%
“…In addition to the acid resistance gene cluster, the L. hongkongensis genome contains two arc gene clusters [arcA (LHK_02729 and LHK_02734), arcB (LHK_02728 and LHK_02733), arcC (LHK_02727 and LHK_02732) and arcD (LHK_02730 and LHK_02731)] of the arginine deiminase pathway which converts L-arginine to carbon dioxide, ATP, and ammonia. The production of ammonia increases the pH of the local environment [26,27]. Similar to other pathogenic bacteria of the gastrointestinal tract, the genome of L. hongkongensis encodes genes for bile resistance.…”
Section: Pathogenic Factorsmentioning
confidence: 99%
“…This ability to carry out arginolysis at low pH allows ADS-positive streptococci to reverse potentially lethal acidi¢cation. When cells of a variety of ADS-positive streptococci were placed in media with arginine at a pH value of 4.0, they were able within a few hours to raise the pH to neutrality and to resume glycolysis and growth [27]. Moreover, if cells were exposed to environments with maintained pH values below 4.0, they were killed rapidly in the absence of arginine but not in its presence.…”
Section: Protection Against Acid Damage and Nutritional Aspectsmentioning
confidence: 99%